Analisis Determinan Statistik Kepatuhan Konsumsi Suplemen Besi: Tinjauan Berdasarkan Faktor Sosiodemografi Remaja Putri - Dian Mustofani; Hariyani Hariyani; Krisnita Krisnita; Hendy Hendy (Mathematics Department, Faculty of Sciences and Technology Unisda Lamongan, 2026)
Female adolescents' compliance in consuming Iron-Folic Acid (IFA) tablets is a crucial pillar of school-based anemia prevention programs. This clinical decision is often assumed to be associated with inherent personal characteristics or social conditioning within their learning environment. To statistically analyze the contribution of school sociodemographic factors (actual age and classroom assignment) as behavioral determinants of iron supplementation compliance among female adolescents. A quantitative study using a cross-sectional design was conducted on 167 female students in grade X at a secondary educational institution. Compliance behavior was measured using a structured Guttman-scaled questionnaire (score 0–4). The association hypothesis was evaluated using the Bivariate Pearson Chi-Square Test () at a significance level of . Univariate analysis showed that age data variance centered on the 16-year-old group (71.9%) and the classroom sample distribution was homogeneous and proportional (21–25 students/class). Bivariate analysis revealed that the Chi-Square coefficient for the actual age variable was with a p-value of 0.080 (). Meanwhile, the coefficient for the classroom assignment variable was with a p-value of 0.093 (). School sociodemographic characteristics (biological age and classroom clustering) are statistically proven not to act as significant determinants of iron supplementation compliance behavior. Students' compliance is purely driven by internal cognitive factors (individual anemia knowledge, which was highly significant in the primary test, ) rather than external demographic attributes. Interventions are recommended to focus on massive and uniform cognitive education.